Peningkatan Pemahaman Iman kepada Nabi dan Rasul melalui Metode Bernyanyi (Joyful Learning) pada Siswa Kelas IV di SDN 07 Padang Matinggi - Gazali Gazali; Yuli Zariai (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to improve students' understanding of faith in Prophets and Messengers through the singing method (Joyful Learning). The background of the research is based on the low learning outcomes of fourth grade students of SDN 07 Padang Matinggi, where only 45% of students were able to achieve completeness on the daily test of memorizing material 25 Prophets and Messengers. This happens because learning is still dominated by the lecture method which makes students quickly bored and less motivated. This study used a Classroom Action Research (PTK) approach which was carried out in two cycles. The research subjects were 34 students, consisting of 14 boys and 20 girls. Data were collected through tests, observations, and documentation, then analyzed descriptively quantitatively and qualitatively. The results showed a significant improvement. In the pre-cycle learning completeness was only 45%, increased to 79% in cycle I, and reached 91% in cycle II. This proves that the singing method is effective in creating a fun learning atmosphere, increasing motivation, and making it easier for students to memorize 25 Prophets and Messengers. Thus, the Joyful Learning method is worth applying in PAI learning, especially in the material of faith in Prophets and Messengers.